Neurobiology of Female Homicide Perpetrators - Brewer-Smyth, Kathleen (Journal of interpersonal violence, 2021)
Neurobiology of female homicide perpetrators is not well understood. Data from private interviews and examinations of females were re-analyzed comparing those who committed homicide (n = 9); other violent crimes, no known homicide (n = 51); nonviolent crimes, no known violent convictions (n = 49); and noncriminals (n = 12). Homicide perpetrators suffered the most childhood sexual abuse (CSA); most recent abuse; had the most neurological histories, mainly traumatic brain injuries (TBIs); most health care access for abuse-related injuries; lowest AM and PM salivary cortisol; and greatest proportion who committed crime under the influence of alcohol. Only CSA, years since last abuse, TBI, neurological histories, and health care access for abuse-related injuries were significant. Those who committed homicide under the influence of alcohol suffered the most recent abuse and had the lowest AM cortisol and flattest diurnal cortisol slope (DCS) compared with others; though the n precludes determining significance. Amount of time since last abuse, AM cortisol and DCS progressively decreased as crime severity increased; other variables progressively increased as crime severity increased. These preliminary findings suggest that low AM cortisol, flat DCS, greater CSA frequency and severity, recent abuse, TBIs, and health care access for abuse-related injuries could be risk factors for females committing homicide. Further study is needed due to the small n of homicide perpetrators. Abuse victims may be at greater risk for alcohol use and cortisol dysregulation associated with perpetrating violence, especially homicide. Frontal lobe damage from TBIs may decrease ability to control behaviors associated with emotions from the limbic system. Health care providers released these women when their abuse-related injuries were not life-threatening; yet, they were life-threatening for victims of their subsequent homicides. Females accessing health care for abuse-related injuries present a critical opportunity for violent crime prevention interventions.